How boards lead small colleges - Brown, Alice W. (Alice Williams), 1942-; Hayford, Elizabeth R. (Johns Hopkins University Press, 2019)
"This professional book (in the Higher Education Leadership Essentials series) encourages presidents of small liberal schools to consider new approaches to working with their boards and offers ideas to trustees about how they can elicit new thinking from their institution's president without interfering in internal operations. Combining theory with case studies, the book is aimed at administrators at colleges (whose boards may include alumni or community members) with operations and interests different from those of university administrators"--